Threat or opportunity? fire response of Gaillardia cabrerae, an endemic species from the south-center of La Pampa province (Argentina) (Semiárida, 2024)
Fires in northern Patagonia are very frequent events, especially in summer seasons, affecting a large percentage of the area each year. Its consequences on biodiversity are variable according to the intensity, permanence and environments that are affected. Fire in ecosystems appears with a dual behavior, as a catastrophic disturbance and as an agent capable of opening environments and allowing the colonization of new sites by rare species, that are considered poor competitors. Through the analysis of measurements in marked plants in the pre-fire season in the Lihué Calel National Park, it was possible to evaluate the response to this phenomenon of Gaillardia cabrerae Covas (Asteraceae), a rarity in the south-central of La Pampa province. The resprouting capacity allowed the recovery of the affected populations and the production of flower heads was recorded in a greater number than in the pre-fire season. These results suggest a positive response of the species to these particular events at the end of 2003. However, given the intrinsic vulnerability of species with such a limited distribution, fire continues to be a high-impact factor for populations and their effect remains uncertain. Considering its rare condition, it is necessary to take precautionary measures to ensure the survival of the species in a context of climate change that defines a near-future scenario characterized by a high degree of unpredictability.
Keywords: Gaillardia cabrerae; rarity; fire response; Lihue Calel National Park; Patagonia